China’s Economic Influence in Central Asia: An Analysis of the Xi Jinping Era (2013-2023) - Saeed, Khalid; Shah, Ali Shan (Annals of Human and Social Sciences, 2024)
This paper examines China’s growing economic power in Central Asia during Xi Jinping’s presidency, specifically the BRI, trade, investment, and energy. The aim is to evaluate the Chinese economic policies introduced into the countries’ infrastructures, financial systems, and political contexts. This study analyses published books and articles, official papers, international trade statistics, and case studies related to Chinese projects in Central Asia. This paper findsout China has raised its economic engagement, creating problems related to relying heavily on loans, adverse effects on the environment, and the labor practices of locals. While China has encouraged regional development, it has also created some economic weaknesses for the Central Asian countries. The recommendation focuses on the diversification of the economic relations, the advancement of the regional integration, and the simplification and the adoption of sustainable development principles to avoid overdependency on China.